Determinants of Violence Against Children in Indonesia: A Literature Review - Dwi Octa Amalia (Universitas Aisyah Pringsewu, 2023)
Violence against children is a public health issue that has implications on a child's health and well-being throughout their lifetime. To prevent violence, it is important to understand the factors associated with violence against children. This literature review aims to determine these factors in Indonesia. A total of 1,025 articles published between 2018-2022 were screened from Garuda, Google Scholar, and DOAJ databases. After applying specific criteria and objectives, 16 articles were selected for this review. This review highlights that there are individual, interpersonal, community, and institutional factors that contribute to violence against children. The individual factors that contribute to violence against children include children's knowledge and attitudes, while interpersonal factors such as parental characteristics and the quality of parent-child relationships. Parental characteristics including education, occupation, socio-economic status, and knowledge, as well as the parent-child relationship in terms of parenting and family environment. Community factor is described through the influence of social media. Institutional factors in schools include the traditional bullying practices, the lack of standard operating procedures, and the social environment. It is essential to consider these factors when developing strategies to prevent violence against children in Indonesia. Abstrak: Kekerasan terhadap anak merupakan masalah kesehatan masyarakat yang memiliki dampak kesehatan pada kesehatan dan kesejahteraan anak di sepanjang hidupnya. Pemahaman mengenai determinan kekerasan anak diperlukan agar dapat dilakukan berbagai upaya pencegahan terjadinya kekerasan pada anak. Literature review ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan kekerasan terhadap anak di Indonesia. Penelusuran artikel melalui database Garuda, Google Scholar, dan DOAJ. Dari 1.025 artikel yang terbit pada tahun 2018-2022, 16 artikel dipilih berdasarkan kriteria dan tujuan kajian. Determinan kekerasan terhadap anak terdiri dari faktor individu, interpersonal, komunitas, dan kelembagaan. Faktor individu meliputi pengetahuan dan sikap anak. Faktor interpersonal meliputi karakteristik orang tua, hubungan anak dengan orang tua dan teman sebaya. Karakteristik orang tua mencakup pendidikan, pekerjaan, status sosio-ekonomi, dan pengetahuan orang tua, serta hubungan anak dan orang tua melalui pola asuh dan lingkungan keluarga. Faktor komunitas digambarkan melalui pengaruh media sosial. Faktor kelembagaan meliputi tradisi bullying, ketidaktersediaan standar operasional prosedur, dan lingkungan sosial di sekolah. Faktor-faktor tersebut perlu dipertimbangkan dalam pengembangan strategi pencegahan kekerasan terhadap anak di Indonesia.